TATUS GIZI IBU DAN JARAK KEHAMILAN DENGAN BADAN LAHIR RENDAH PADA BAYI - Sriami .; Churatul Resa Yuni Andari (JURNAL PENELITIAN KESEHATAN, 2014)
This study aimed to explore the relationship between maternal nutritional status and spacing of pregnancy with the incidence of low birth weight babies in hospitals Syarifa Ambami Rato Ebu, Bangkalan.The study was cross sectional correlation with the independent variables maternal nutritional status and the dependent variable spacing pregnancies and low birth weight. Its population is all women giving birth in hospitals Syarifa Ambami Rato Ebu, Bangkalan the 127 mothers. Sample taken at random gained 96 people, a large sample is taken with probability sampling technique and then proceed with proportional random sampling. Data collection using the documentation status of the patient. Then analyzed by Chi-Square Test with a significant level of ≤ 0.05. ri The results for the variable of maternal nutritional status during pregnancy is not the risk of having a baby with BBL KEK normal with 72.41% and maternal risk of having a baby with BBL KEK low 63.15%. And the results of the statistical test Chi-Square Test showed ρ α (0.05 ≤ 0.001). As for the variable spacing of 2 years of having a baby with normal BBL 75% and maternal pregnancy distance 2 years of having a baby with low BBL 69.44%. And the results of the statistical test Chi-Square Test showed ρ α (0.05 ≤ 0.000).By inference, there is a relationship between maternal nutritional status and pregnancy spacing with low birth weight incidence in infants in hospitals Syarifa Ambami Rato Ebu, Bangkalan. Health care workers should continue to provide counseling to pregnant women routinely about nutrition and good spacing pregnancies. Thus, pregnant women always consider the risk factors that could cause the LBW. Keywords: Nutritional status, distance Pregnancy, LBW